'A Blemish on the History of the Twentieth century'? Legends and Fabrications Surrounding the Mass Cremations in the Wake of the Dresden Air Raids, February 1945. (2nd October 2018) - Weber, Christoph D.
Abstract : Whereas the myths that emerged in the wake of the Dresden bombings in February 1945 have undergone scholarly scrutiny, no comprehensive analysis has yet been undertaken of how the mass cremations of the bombing victims on the Altmarkt, Dresden's old market square, have been remembered in post-war Germany. Scholars have associated the stacking of corpses onto funeral pyres with Jews burned in the Middle Ages and with the burning of Jewish victims at the Treblinka killing centre. This conflation of atrocities, which has contributed to the myth-making surrounding Dresden's destruction, has its basis in the misappropriation of historical sources.